Sex-Specific Functional Connectivity in the Reward Network Related to Distinct Gender Roles - Du, Yin; Wang, Yinan; Yu, Mengxia; Tian, Xue; Liu, Jia (Frontiers in Human Neuroscience, 2021)
Gender roles are antidichotomous and malleable social constructs that should theoretically be constructed independently from biological sex. Yet, it is unclear whether and how the factor of sex is related to neural mechanisms involved in social constructions of gender roles. Thus, the present study aimed to investigate sex specificity in gender role constructions and the corresponding underlying neural mechanisms. We measured gender role orientation using the Bem Sex-Role Inventory, used a voxel-based global brain connectivity (GBC) method based on resting-state functional magnetic resonance imaging to characterize the within-network connectivity in the brain reward network (RN), and analyzed how the integration of the RN is related to gender role scores between sex groups. An omnibus analysis of voxel-wise GBC values within a two-level linear mixed model (LMM) revealed that in female participants, femininity scores were positively associated with integration in the posterior orbitofrontal cortex and subcallosal cortex (SCC), whereas masculinity scores were positively associated with integration in the frontal pole. By contrast, in male participants, masculinity was negatively correlated with integration in the nucleus accumbens and SCC. For the first time, the present study revealed the sex-specific neural mechanisms underlying distinct gender roles, which elucidates the process of gender construction from the perspective of the interaction between reward sensitivity and social reinforcement.